2016
DOI: 10.15376/biores.11.1.2492-2503
|View full text |Cite
|
Sign up to set email alerts
|

Method for Forming Pulp Fibre Yarns Developed by a Design-driven Process

Abstract: A simple and inexpensive method for producing water-stable pulp fibre yarns using a deep eutectic mixture composed of choline chloride and urea (ChCl/urea) was developed in this work. Deep eutectic solvents (DESs) are eutectic mixtures consisting of two or more components that together have a lower melting point than the individual components. DESs have been previously studied with respect to cellulose dissolution, functionalisation, and pre-treatment. This new method uses a mixture of choline chloride and ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 21 publications
2
30
1
Order By: Relevance
“…The cellulose fiber yarn used in this study was prepared by using a deep eutectic solvent (DES) as a spinning medium, as described elsewhere. 9 Briefly, never dried cellulose fibers were first washed to sodium form by lowering the pH of the suspension (to pH 2 with hydrochloric acid). After one-hour acid treatment, the fibers were washed several times with deionized water followed by titration into the sodium form by addition of NaHCO 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellulose fiber yarn used in this study was prepared by using a deep eutectic solvent (DES) as a spinning medium, as described elsewhere. 9 Briefly, never dried cellulose fibers were first washed to sodium form by lowering the pH of the suspension (to pH 2 with hydrochloric acid). After one-hour acid treatment, the fibers were washed several times with deionized water followed by titration into the sodium form by addition of NaHCO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The fiber yarn, carrying 10% PAA, was cross-linked by using a laboratory oven (140 °C for 30 min) following the procedure presented earlier by us. 33 The detailed procedure and analyses of the fiber yarn properties can be found in Tenhunen et al 9 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason behind this is the lack of cohesion due to the deterioration of hydrogen bonding among the wet WNFs. It has been reported that, when wet, hydrogen bonding plays a role in strength (Tenhunen et al, 2016). WNFs are covered by lignin, which can form hydrogen bonds (Kubo & Kadla, 2005), but not as extensively as CNFs which have a large number of hydroxyl groups.…”
Section: Draining Time and Ease Of Nanopaper Preparationmentioning
confidence: 99%
“…The strength of the LF-CMC composite filaments achieves the levels required in many filament applications. As an example, cotton filament and pulpbased fibre filament crosslinked with polyacrylic acid (PAA) have been reported to reach a tenacity level of 15 and 5 cN/tex, respectively (Tenhunen et al 2016). However, the prepared filaments did not achieve the strength level of regenerated cellulose filaments made by NaOH/urea carbamate or by novel ionic liquid processes (tenacities up to 37 cN/tex) (Qi et al 2008;Hauru et al 2014).…”
Section: Characterisation Of Produced Lf Gradesmentioning
confidence: 99%